2016
DOI: 10.1002/jbm.a.35672
|View full text |Cite
|
Sign up to set email alerts
|

Polyampholyte‐ and nanosilicate‐based soft bionanocomposites with tailorable mechanical and cell adhesion properties

Abstract: Engineered tissues are excellent substitutes for treating organ failure associated with disease, injury, and degeneration. Designing new biomaterials with controlled release profiles, good mechanical properties, and cell adhesion characteristics can be useful for the formation of specific functional tissues. Here, we report the formulation of nanocomposite hydrogels based on carboxylated poly-l-lysine and synthetic clay laponite XLG in which four-arm polyethylene glycol with N-hydroxy succinimide ester (PEG-NH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“…Various factors have been suggested as possible mechanisms behind clay-enhanced cell adhesion and spreading. Indirect enhancement of cell adhesion via the adsorption of cell adhesive proteins such as fibronectin or vitronectin from serum supplemented media is frequently cited and likely to play a role 103,104,112,113 . Interestingly though, even in serum-free media, fibroblast attachment and spreading was observed on PEO/clay surfaces following a clay concentration dependent trend.…”
Section: Cell Adhesion and Proliferationmentioning
confidence: 99%
See 1 more Smart Citation
“…Various factors have been suggested as possible mechanisms behind clay-enhanced cell adhesion and spreading. Indirect enhancement of cell adhesion via the adsorption of cell adhesive proteins such as fibronectin or vitronectin from serum supplemented media is frequently cited and likely to play a role 103,104,112,113 . Interestingly though, even in serum-free media, fibroblast attachment and spreading was observed on PEO/clay surfaces following a clay concentration dependent trend.…”
Section: Cell Adhesion and Proliferationmentioning
confidence: 99%
“…Such divalent ions are essential for the function of integrins, the transmembrane receptors that mediate cell interactions with ECM 116 . It has also been suggested that Mg 2+ ions arising from the dissolution of Laponite could promote cell adhesion 112,117 , however, the concentration of clay dissolution expected in physiological buffers is disputed 118 and the concentration of divalent ions in cell culture media is also unlikely to be limiting.…”
Section: Cell Adhesion and Proliferationmentioning
confidence: 99%
“…Carboxylated poly‐ l ‐lysine (COOH‐PLL) is a polyampholyte and has been reported to possess excellent cryopreservation ability when it contains the amino and carboxyl groups in a suitable ratio (i.e., in amounts of 35 and 65 mol %, respectively) …”
Section: Introductionmentioning
confidence: 99%
“…27 Carboxylated poly-L-lysine (COOH-PLL) is a polyampholyte and has been reported to possess excellent cryopreservation ability when it contains the amino and carboxyl groups in a suitable ratio (i.e., in amounts of 35 and 65 mol %, respectively). [15][16][17][28][29][30] Here we report that the poly-L-lysine-based polyampholyte COOH-PLL shows thermoresponsiveness at its critical temperature and that its critical temperature can be tuned readily by changing its hydrophobicity and charge ratio via simple molecular design. We had previously reported that COOH-PLL shows high cryoprotectiveness 15 and hence can be used as a cryoprotectant and that it can form hydrogels and thus be used for cell encapsulation in tissue engineering and drug delivery.…”
mentioning
confidence: 99%
“…However, this study clearly demonstrated the easily tuned mechanical properties of polyampholyte systems with low crosslinker densities. In a similar fashion, Jian and Matsumura were able to controllably tune the mechanical properties of their nanocomposite hydrogel designed with carboxylated poly- l -lysine (COOH-PLL), and synthetic clay laponite XLG, by changing the laponite concentration (composition dependence) or the density of the polyethylene glycol with N -hydroxy succinimide ester (PEG–NHS) crosslinker [17]. Changing the crosslinker density or monomer concentration are also common tuning mechanisms for mechanical properties [18,19,20,21,22].…”
Section: Mechanical Propertiesmentioning
confidence: 99%